Curriculum design of college students' English critical ability in the internet age - Shen, Jie (2022)
"Speculation"is considered to be one of the important qualities that modern students should possess, and it is also the goal of modern education. With the advent of the Internet age, teaching models have been continuously combined with technology. From mixed teaching to flipped classroom, teaching with different methods of information transmission can achieve the best results. This paper is aimed at studying the curriculum design of college students' English critical thinking ability in the Internet era. On the basis of analyzing the significance of cultivating college students' critical thinking ability and the curriculum design of critical thinking ability, the flipped classroom mode is used for teaching practice through the experimental method and questionnaire survey method. The personality tendency and the cultivation of students' critical thinking ability in the flipped classroom were analyzed statistically. Finally, it was concluded that the students' critical thinking skills have been improved to a certain extent through the various links set in the flipped classroom teaching.